2022
DOI: 10.1097/sla.0000000000005722
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Postoperative Mortality Among COVID-19 Positive Patients: Results of 3027 Operations and Procedures

Abstract: Objective: To investigate the predictors of postoperative mortality in coronavirus disease 2019 (COVID-19)-positive patients. Background: COVID-19-positive patients have more postoperative complications. Studies investigating the risk factors for postoperative mortality in COVID-19-positive patients are limited. Methods: COVID-19-positive patients who underwent surgeries/procedures in Cleveland Clinic between January 2020 and March 2021 were identified retrospectively. The primary outcome was postoperative/pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…It may not be possible to defer emergency or urgent surgery for this suggested period. Recent studies have also observed an increased risk of mortality after emergency surgery [HR 6.35, (3.39,11.89), p-value < 0.001] in COVID-19 patients as compared to elective surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may not be possible to defer emergency or urgent surgery for this suggested period. Recent studies have also observed an increased risk of mortality after emergency surgery [HR 6.35, (3.39,11.89), p-value < 0.001] in COVID-19 patients as compared to elective surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical or conservative treatment of emergency patients should be considered first, wherever feasible and safe. As the risk of death at 30 days postoperatively is 6.35 times higher for emergency surgery than for elective surgery in patients with a positive COVID-19 infection, [10] non-surgical management of patients with a positive COVID-19 infection is strongly recommended. Assessment of emergency patients should not be delayed in order to determine novel coronavirus infection status, and it is recommended that involved healthcare workers should strictly wear personal protective equipment.…”
Section: Emergency Surgerymentioning
confidence: 99%
“…The risk is highest for cardiothoracic surgery, with the risk of death at 30 days postoperatively being 2.01 times higher than gastrointestinal surgery. [10] Therefore, the cardiopulmonary function should be carefully assessed preoperatively for patients undergoing elective cardiothoracic surgery. In a study of children undergoing surgery for congenital heart disease, no difference was found in the incidence of postoperative complications between COVID-19 positive children who underwent surgery 6 weeks after recovery and COVID-19 negative children.…”
Section: Additional Considerations In Scheduling Elective Surgical Pr...mentioning
confidence: 99%
“…5-9 Among patients infected with COVID-19 and undergoing surgery, the risk factors for postoperative complications include the time to surgery after COVID-19 infection, 10 vaccination status, 11 comorbidities, 12 male sex, 13 and advancing age. 12 The SARS-CoV-2 virus can cause endothelial damage and immunosuppression, resulting in a higher incidence of postoperative thromboembolism and infectious complications. 10,14…”
Section: Introductionmentioning
confidence: 99%